The First Rei Organometallic Complex with an Organoimido-Polyoxometalate Ligand - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Wrighton-Araneda, K (Royal Society of Chemistry, 2017)
The spectroscopic, electrochemical and photophysical properties of the first ReI organometallic organoimido-polyoxometalate complex [n-Bu4N][Mo6O18NC6H4-CH2-N3C2H2-Re-phen(CO)3] compared with all fragments are reported. The UV-Vis spectra are analysed using experimental and theoretical tools. In contrast to the reported studies in the literature, our results show that a new more intense band is present in the spectra of the hybrid ligand obscuring the intra-polyanion charge transfer. The electrochemical results show that the strong acceptor character of the polyoxometalate fragment is quenched by the condensation of the phenyl-triazole molecule. © 2017 The Royal Society of Chemistry.